Experimental investigation on the hydrodynamic response of a moored ship to low-frequency harbor oscillations. (15th October 2022) - Dong, Guohai; Yan, Mingyu; Zheng, Zhenjun; Ma, Xiaozhou; Sun, Zhongbin; Gao, Junliang
Abstract: Low-frequency harbor oscillations can lead to large motions of moored vessels, resulting in port downtime, damage to ships, and even casualties. Aiming at the operational problems encountered in the Hambantota Port caused by low-frequency oscillations, a series of physical experiments were implemented to investigate the effect of long-wave-induced harbor oscillations on a moored ship. Four natural periods of the harbor were identified by combining the time- and frequency-domain analyses of the wave surface elevations. The spatial characteristics of these natural modes are further analyzed using a mild-slope equation model. Subsequently, the time- and frequency-domain characteristics of the ship motions and the correlations of ship motions with the waves at various frequency bands were determined. The results show that the horizontal motions of the ship (i.e., surge, sway, and yaw) are controlled by the low-frequency wave energy, whereas the vertical motions (i.e., heave, roll, and pitch) are governed by the short-wave energy. Moreover, a significant correlation is observed between the low-frequency waves and horizontal motions, based on which parametric formulas were proposed to estimate the surge and sway motions and to improve the port operation positively. Highlights: The effect of low-frequency oscillations induced by long-period waves on the motions of moored ships was systematically investigated. The dominant factors of low frequency oscillation within the harbor are investigated. The influence of longitudinal and transverse natural modes of harbor oscillations on ship motions is investigated. The characteristics of moored ship motions under low-frequency oscillations are revealed. The influence of waves in different band of berth on ship motion is analyzed and used parametric formulas for the rapid estimation of motions.